2022
DOI: 10.1093/function/zqac029
|View full text |Cite
|
Sign up to set email alerts
|

The Link Between Childhood Adversity and Cardiovascular Disease Risk: Role of Cerebral and Systemic Vasculature

Abstract: Adverse childhood experiences (ACEs) are traumatic events during the first years of life that are associated with a higher risk of developing cardiovascular disease (CVD) during adulthood. The medial prefrontal cortex (mPFC) is a core region in the brain that modulates emotions and is directly involved in the cardiovascular response to stress by increasing vascular resistance. In the present study we examined the relationship between ACEs, mPFC and peripheral vascular function. Forty-five, adults (33±5 yrs.) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Specifically, young adult women (∼20 years old) with moderate-to-severe (≥4) ACE exposure exhibited endothelial dysfunction, as measured by the flow mediated-dilation (FMD) technique. Rodriguez-Miguelez and colleagues 3 confirmed the finding of impaired FMD in a cohort of young adult men and women (∼32 years old) and extended these findings by performing comprehensive assessments of medial prefrontal cortex (mPFC) blood flow, microvascular function, and arterial stiffness.…”
Section: A Perspective On “The Link Between Childhood Adversity and C...mentioning
confidence: 72%
See 1 more Smart Citation
“…Specifically, young adult women (∼20 years old) with moderate-to-severe (≥4) ACE exposure exhibited endothelial dysfunction, as measured by the flow mediated-dilation (FMD) technique. Rodriguez-Miguelez and colleagues 3 confirmed the finding of impaired FMD in a cohort of young adult men and women (∼32 years old) and extended these findings by performing comprehensive assessments of medial prefrontal cortex (mPFC) blood flow, microvascular function, and arterial stiffness.…”
Section: A Perspective On “The Link Between Childhood Adversity and C...mentioning
confidence: 72%
“…Despite the pervasiveness of ACEs and robust evidence supporting the association between ACEs and CVD, our current understanding of how ACEs promote CVD is limited. In this issue of Function , Rodriguez-Miguelez and colleagues 3 provide important evidence to further reveal how ACEs ‘get under the skin’ to promote CVD.…”
Section: A Perspective On “The Link Between Childhood Adversity and C...mentioning
confidence: 99%
“…An emerging body of literature suggests that chronic psychosocial stress contributes to premature vascular dysfunction. [265][266][267][268] Alarmingly, the prevalence of posttraumatic stress disorder is particularly high among PLWH, with estimates ranging from 23% to 42%. 269,270 Further, 2 separate cohort studies reported that >50% of PLWH in the United States have a history of childhood physical or sexual abuse.…”
Section: Psychosocial Stress Mood Stress Disorders and Accelerated Va...mentioning
confidence: 99%